Síntese e caracterização de filmes do sistema Zn(1−x)CoxO obtidos por spray pirólise - Onofre Ramirez, Yina Julieth (Universidade Federal de São Carlos, 2016)
We report a systematic study on the structural, morphological and optical properties of Zn1−xCoxO thin films grown by spray pyrolysis. The employed nominal concentrations were up to 15 Co %. The films were deposited on glass substrates between 220-300 o C using precursors such as zinc acetate and cobalt acetate in aqueous solutions. The effects of Co-doping on structural, morphological and optical properties were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical transmittance and absorbance as well as photoluminescence (PL). The XRD results indicated that all films are polycrystalline with wurtzite crystal structure, a preferential growth direction in c-axis, and no secondary phases. SEM images generally showed uniform surface, and few regions have irregularities due to effects of the inclusion of cobalt as well as substrate deposition temperature. The spectra of transmittance and absorbance exhibited the transitions d-d due to Co2+ ion, a redshift of the absorption-edge and changes in the absorption band intensity with increasing of nominal Co-doping. These observations revealed the substitution of Zn ions Zn2+ and the presence of Co in the state 2+ in tetrahedral coordination in the ZnO lattice. Furthermore, there was a narrowing in band gap of 28 meV by percentage of Co inserted into the lattice. The PL spectra of ZnCoO samples presented three bands associated to near-band-edge absorption (NBE), structural defects and intratomic emissions of Co2+. Their optical emissions were characterized by the presence of traps which capture carriers and affect significantly the emissions. Through a qualitative model in a temperature range we interpreted these traps as potential fluctuations up to 17 meV. We also discussed the annealing in selected samples.
Keywords: Semicondutor magnético diluído; Óxido de zinco; Spintrônica; Spray pirólise; Diluted magnetic semiconductor; Zinc oxide; Spintronic; Spray pyrolysis; CIENCIAS EXATAS E DA TERRA::FISICA